G384 Predictive value of the Kobayashi Score for IVIG resistance in Kawasaki Disease in the UK. (7th April 2014) - Sutton, N; Davies, S; Levin, M
Abstract : Aims: The Kobayashi score, based on clinical and laboratory data, successfully predicts resistance to intravenous immunoglobulin (IVIG) treatment in children with Kawasaki Disease (KD) in a Japanese setting, where it is used to identify children who will benefit from early corticosteroid administration. We used a retrospective case review to test the ability of the Kobayashi Score to predict IVIG resistance and coronary artery aneurysm (CAA) development in children treated for KD at a single London centre. Methods: Children treated for KD during a 7-year period 2005–2012 were identified by their discharge diagnosis. Of 59 children identified, 51 had case notes available. Clinical, laboratory, demographic and echocardiography data were recorded, and the Kobayashi score at presentation (pre-IVIG) was calculated. Categorical data were analysed with Fishers Exact test. Results: Of 51 cases, 70% fulfilled criteria for complete KD, and 30% had incomplete criteria at the time of IVIG treatment. 67% of cases were male. The mean age was 27 months, (range 3–96 months). A combination of white, black, asian and mixed ethnicities were represented. Seven cases were excluded from subsequent analysis because of incomplete information for calculation of the Kobayashi scores. Of 44 remaining cases, 30 were identified as high risk (score ≥4) and the mean score was 4.75. 16/44 required second-line treatment for on-going fever after initial IVIG but this was not predicted by a high Kobayashi score (10/16 vs 20/28 with score ≥4; p = 0.73). 15 had CAA or coronary artery dilatation evident at echo (11/15 vs 19/29 with score ≥4; p = 0.74). Conclusion: We analysed 44 KD cases from a single UK centre and found no evidence that the Kobayashi Score predicts IVIG resistance, or CAA and coronary artery dilatation. Whilst there is evidence to support the predictive value of the Kobayashi score in Japan, this was not replicated in a US study. Our data support the need to devise a new score for use outside Japan, that can identify children unlikely to respond to IVIG who are at increased risk of CAA without early additional treatment.